Pelatihan Higiene dan Sanitasi Makanan pada Pedagang Makanan di Kantin SD - Jamilatur Rohmah; Siti Cholifah; Vanda Rezania (IAI Darussalam, 2019)
The school canteen has an important role to fulfill the food needs of school children. In general, foods that are sold in canteens have very diverse variations, with prices relatively cheap and easily accessible to school children. The need for fulfillment of hygienic foods is ordered by the factors of place and hygiene of the food handlers need to be done. Foods that do not meet the requirements and safety that can be given due to health problems or diseases related to food such as diarrhea, cholera, dysentery, typhus, and other food poisoning. The number of food handlers in the cafeteria of SD Muhammadiyah 1 and 2 Sidoarjo competes 6 people. Based on the results of observations and interviews, they did not have sufficient educational background in terms of hygiene and food sanitation, and they never gained knowledge about food hygiene and sanitation. This will greatly determine the quality of food provided to consumers especially elementary school children. Based on this, the Community Service activities on hygiene training and food sanitation were carried out at food handlers in the cafeteria of Muhammadiyah 1 and 2 elementary schools in Sidoarjo.